2021
DOI: 10.1002/jsfa.11469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flooding cultivation on the composition and quality of taro (Colocasia esculenta cv. Daikichi)

Abstract: BACKGROUND: Taro (Colocasia esculenta cv. Daikichi) is believed to be one of the earliest cultivated tuber crops and it is a staple food in many parts of the world. The mother corm and side cormels (daughter and granddaughter tubers) form the major consumed parts; however, the former is rarely preferred. Taro is mainly cultivated using either unflooded or flooding cultivation, under dryland-rainfed and wetland-irrigated conditions, respectively. Although flooding cultivation has several advantages, such as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cooked meat samples (beef, pork, and duck) were comprehensively evaluated for the following sensory attributes: sweetness, bitterness, hardness, and umami. Each item was rated on a five-point scale, with scores ranging between + 2 and -2 27 . Higher scores reflect sweeter and stronger umami tastes, less bitterness, and more tenderness.…”
Section: Nutrient Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cooked meat samples (beef, pork, and duck) were comprehensively evaluated for the following sensory attributes: sweetness, bitterness, hardness, and umami. Each item was rated on a five-point scale, with scores ranging between + 2 and -2 27 . Higher scores reflect sweeter and stronger umami tastes, less bitterness, and more tenderness.…”
Section: Nutrient Analysismentioning
confidence: 99%
“…Data are presented as the mean ± standard deviation. P < 0.05 was considered statistically significant 27 .…”
Section: Nutrient Analysismentioning
confidence: 99%
“…This study only looked at "full-dykes' ', that is, high and strong dykes; therefore, there is a need to provide an indepth understanding of the influence of all forms of dykes, including low and weak ones, on food crop production. Yamanouchi et al (2022) & Adam (2008 revealed that arable farming had intensified since the middle of the 18th century, and by 1850, 60-80% of the coastal marshes were used for cereal production and the acreage of winter cereals had increased as well. Natural grasslands were replaced.…”
Section: Introductionmentioning
confidence: 99%
“…The agriculture industry should utilize clean water to its full potential without being squandered. Irrigation systems should give an amount of water that corresponds to the needs of plants, such as taro yam (Colocasia esculenta), for which water should be kept at a depth of 2.5 to 5.0 cm when new roots are developing and the first leaves appear [19]- [21]. Hence, crops require a specific amount of water, and the existing system cannot supply the correct amount of water.…”
Section: Introductionmentioning
confidence: 99%